Crecimiento inclusivo y empleos dignos por género: El caso de las áreas urbanas de Bolivia - Beatriz Muriel Hernández; Sergio Mansilla (Institute for Advanced Development Studies (INESAD), 2023)
– This paper presents an empirical study of how inclusive was the extraordinary growth experienced by Bolivia between 2006 and 2019, in terms of decent job generation in urban areas and by gender. For this, we use the Ali and Son (2007) concentration curve of opportunities and approach the jobs with five rates proposed by Muriel (2014, 2019, 2020a, 2020b): i.e. job stability, Christmas wage bonus tenure, social protection access, sufficient labour income and membership of a labour association. The results show that growth was inclusive between 2006 and 2011; but it was not in further periods. Even, the percentage of workers with Christmas wage bonus, sufficient labor income and with affiliation to some labor association were lower in 2019 compared to 2006. In terms of gender gaps, the one associated with sufficient labor income stands out, but the main problems lie in the inequities of access to opportunities within the same female population.
Keywords: D63; J16; J29; J39; J83; 330; Decent jobs; inclusive growth; gender